China’s African Financial Engagement, Real Exchange Rates and Trade between China and Africa - (:unkn) unknown (My University, 2015)
In the last decade, China’s trade with Africa increased faster than its overall foreign trade. This article focusses on the role of real exchange rates in this growth. A ‘bilateral real exchange rate’ augmented trade gravity model applied to China’s trade with 49 African countries over the period 2000–2011 shows that the real appreciation of most African currencies relative to the renminbi favoured China’s exports to these countries, but had no impact on China’s imports from Africa. This real appreciation of African currencies is explained by three main factors: the decision to peg themto other currencies (in particular to the euro), the amount of export of raw materials from African countries and the amount of financial assistance from international donors including China. Thus, a kind of detrimental sequence exists in Africa’s relationship with China: China’s imports of raw materials and its economic co-operation are among the factors explaining the appreciation of African real exchange rates, which itself stimulates China’s exports of manufactured goods, and so restricts Africa’s own industrial development.
Keywords: African Research